Effects of low- and high-calcium fly ash on magnesium oxysulfate cement. (10th August 2019) - Zhang, Na; Yu, Hongfa; Wang, Nan; Gong, Wei; Tan, Yongshan; Wu, Chengyou
Highlights: Using L-FA and H-FA in MOSC achieves beneficial effects. The possibility of using H-FA in MOSC is confirmed. The MOSC with H-FA has good volume stability and a denser microstructure. Compared with L-FA, the incorporation of H-FA into MOSC increases the 5·1·7/Mg(OH)2 ratio in the hydration products. Abstract: Magnesia-based cementitious materials have a reputation for being "green engineering materials in the 21st century". By incorporating fly ash (FA) into magnesium oxysulfate cement (MOSC), a new type of high performance MOSC that achieves energy savings and environmental protection can be produced for industrial construction applications. In this paper, the performance of MOSC with low-calcium fly ash (L-FA) and high-calcium fly ash (H-FA) was investigated, including the setting times, compressive strengths, shrinkages, compositions and microstructures. The results show that adding FA to MOSC can accelerate the hydration reaction and improve the volume stability of the MOSC paste. The high compressive strength of MOSC is derived from the sound composition and compact microstructure of the hydration products. The large water requirement of the fine H-FA particles in H-FM and the resulting filling effect are beneficial to the optimization of the composition of the hydration product and the formation of dense microstructures, respectively, which make the MOSC with H-FA possess excellent setting characteristics, high compressive strength, good volume stability and a compact microstructure. These results confirm the feasibility of applying H-FA in MOSC. Therefore, both types of FA can be used as a major component of MOSC, and the dose can be up to 50% of MgO weight or more, which improves the technological, economic and environmental benefits.